2017
DOI: 10.1016/j.fertnstert.2017.02.113
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of intrauterine adhesions after the application of hyaluronic acid gel after dilatation and curettage in women with at least one previous curettage: short-term outcomes of a multicenter, prospective randomized controlled trial

Abstract: NTR 3120.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
61
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(64 citation statements)
references
References 30 publications
2
61
0
1
Order By: Relevance
“…A total of seven were included in the final analysis after screening ( Fig. 1) (10,(13)(14)(15)(16)(17)(18). All 7 studies compared the efficacies of using hyaluronic acid gel as an adjuvant therapy (treatment group) against a control group (without the use of hyaluronic acid gel) after an intrauterine operation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of seven were included in the final analysis after screening ( Fig. 1) (10,(13)(14)(15)(16)(17)(18). All 7 studies compared the efficacies of using hyaluronic acid gel as an adjuvant therapy (treatment group) against a control group (without the use of hyaluronic acid gel) after an intrauterine operation.…”
Section: Resultsmentioning
confidence: 99%
“…From these patients, 455 had been treated with hyaluronic acid gel postoperatively and 497 were controls. Among the 7 studies, 3 used common abortive procedures such as intrauterine operations (14,15,17) and 4 were performed using hysteroscopy (10,13,16,18). A total of six studies were performed using direct injection with the gel (10,16,18) and one used a temporary adhesion barrier, which hydrated into a gel within 24-48 h of administration into the patient (17).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Only one trial, conducted by Hooker et al [9], reported complications associated with use of hyaluronic acid gel. The major complications were patient discomfort and uterine perforation, with no statistically significant differences between the 2 groups.…”
Section: Resultsmentioning
confidence: 99%
“…dilatation and curettage), resection of endometrial polyps, and resection of the uterine cavity septum. 3,4 In addition, cesarean delivery, pelvic inflammatory disease, endometrial tuberculosis, and uterine artery embolism can also cause intrauterine adhesion. 5,6 Hysteroscopic adhesiolysis and adjuvant therapies-including hormones, intrauterine devices, intrauterine balloons, gels, and early secondary hysteroscopy-have been moderately successful in treating intrauterine adhesions.…”
Section: Introductionmentioning
confidence: 99%